High School Students Understanding of the Risks of Online Game Addiction - Eryzal Novrialdy; Herman Nirwana; Riska Ahmad (RedWhite Press, 2019)
Adolescents are currently in the midst of technological sophistication, which is very helpful for its development. On the other hand, many adolescents are trapped in the problem of technology addiction. Adolescents are the most age group who experience problems with the use of technology, including online games. Online game addiction is the loss of control over the use of online games, which makes other daily activities are disrupted. Online game addiction in adolescents have an impact on several aspects of life, such as health aspects, psychological aspects, academic aspects, social aspects, and financial aspects. Lack of understanding about the risks of online game addiction can get adolescent stuck in online game addiction. This research aims to describe high school students understanding about the risks of online game addiction. The sample consisted of 255 high school students selected by proportional random sampling technique. Data was collected using a scale measuring understanding of the risks of online game addiction. Data analysis used a quantitative approach with descriptive methods. The results showed that high school students understanding about the risks of online game addiction was included in the moderate category with an average score of 198,48 and an achievement score level of 55,14%. Therefore, school counselors must to improve high school students understanding of the risks of online game addiction.